Application and Development of Big Data in Chinese Business Education - Yang, Zhaowen (Technium Social Sciences Journal, 2021)
Despite the challenges facing Chinese business education amid COVID-19, there are trends and opportunities for business educational internationalization after COVID-19. The pandemic has acted as a catalyst for learning institutions in China to look for innovative solutions in a short period. In addition to this, the pandemic has grown public-private business-education partnerships. It will create a blended learning environment that can generate a better educational experience with more than 100 percent face-to-face learning. Furthermore, quality learning and teaching materials will be widely used and well-curated after the pandemic.